ONE, TWO OR MANY IMPERIALISMS? - Korolija, Aleksandar (National interest, 2023)
The paper problematizes the understanding of the concept of imperialism in the current conjuncture, which is significantly determined by the Ukrainian crisis. In particular, the position of some of the leading left-wing intellectuals is criticized, with the claim that they omit the meaning that imperialism had in classical Marxist theory, as well as structural unequal power relations and unequal socio-economic development that characterizes the modern world capitalist system. By criticizing these positions, an attempt is made to start a broader theoretical debate about what the term imperialism should mean in contemporary (geo)political circumstances. In this context, the position of China is considered, which is presented in the paper as a semiperiphery country that is not imperialistic and that does not have a project of a new global hegemony. It is concluded that there is currently only one imperialism and the only global hegemonic project under the leadership of the USA.